2001
DOI: 10.4049/jimmunol.167.4.2040
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Alterations in Activation-Induced Nonresponsive CD8 T Cells

Abstract: Costimulation-dependent production and autocrine use of IL-2 by activated CD8 T cells results in initial clonal expansion, but this is transient. The cells quickly become anergic, unable to produce IL-2 in response to Ag and costimulation, irrespective of the form of costimulation. This activation-induced non-responsiveness (AINR) differs from “classical” anergy in that it results despite the cells receiving both signal 1 and signal 2. AINR cells can still proliferate in response to exogenous IL-2, but can no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
1
2

Year Published

2007
2007
2009
2009

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 45 publications
1
47
1
2
Order By: Relevance
“…The addition of exogenous IL-2 can reverse AINR, which has been characterized to result from impaired TCR-induced MAPK activation (including ERK) and IL-2 production (47)(48)(49). We found that cultures of stimulated gal-1-deficient CD8 cells produce more IL-2 than their wild-type counterparts.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The addition of exogenous IL-2 can reverse AINR, which has been characterized to result from impaired TCR-induced MAPK activation (including ERK) and IL-2 production (47)(48)(49). We found that cultures of stimulated gal-1-deficient CD8 cells produce more IL-2 than their wild-type counterparts.…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies by Mescher and colleagues (47)(48)(49) have identified a period of activation-induced nonresponsiveness (AINR) in CD8 T cells 2-4 days after initial TCR engagement, wherein CD8 T cells become unable to produce IL-2 or proliferate in response to secondary TCR engagement. The addition of exogenous IL-2 can reverse AINR, which has been characterized to result from impaired TCR-induced MAPK activation (including ERK) and IL-2 production (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…Defects in activation of all three of these MAPKs were seen in AINR CD8 T cells [68]. Initial activation of ERK (1 min) was comparable in normal and AINR cells, but activity declined much more rapidly in AINR cells.…”
Section: The Molecular Basis For the Ainr Statementioning
confidence: 88%
“…Treatment of AINR cells with phorbol myristic acetate (PMA), an activator of ras and PKC, and ionomycin, a calcium ionophore, activated ERK, JNK and p38 and stimulated IL-2 production and proliferation by the cells, and the proliferation was inhibited by ERK and p38 inhibitors [68]. These results suggest that cells in the AINR state are unable to activate p21 ras via TCR and CD28 signaling, although this has not yet been directly demonstrated.…”
Section: The Molecular Basis For the Ainr Statementioning
confidence: 96%
See 1 more Smart Citation